Inexpensive Measuring System for the Characterization of Organic Transistors - Clara Pérez-Fuster (Journal of Sensors, 2018)
A measuring module has been specifically designed for the electrical characterization of organic semiconductor devices such as organic field effect transistors (OFETs) and organic electrochemical transistors (OECTs) according to the IEEE 1620-2008 standard. This device has been tested with OFETs based on 6,13-bis(triisopropylsilylethinyl)pentacene (TIPS-pentacene). The measuring system has been constructed using a NI-PXIe-1073 chassis with integrated controller and two NI-PXI-4132 programmable high-precision source measure units (SMUs) that offer a four-quadrant ± 100 V output, with resolution down to 10 pA. LabVIEW™ has been used to develop the appropriate program. Most of the main OFET parameters included in the IEEE 1620 standard can be measured by means of this device. Although nowadays expensive devices for the characterization of Si-based transistors are available, devices for the characterization of organic transistors are not yet widespread in the market. Fabrication of a specific and flexible module that can be used to characterize this type of transistors would provide a powerful tool to researchers.